(untitled) (Swiss Medical Weekly, 2017)
QUESTIONS Published studies lack clear indicators of risk and predictors of transition from Raynaud’s phenomenon (Rp) to connective tissue diseases (CTDs). Therefore, we aimed to study the outcomes, rates and predictors of transition to CTDs in patients with Rp. METHODS A sensitive search was developed in Medline and Embase. Observational studies reporting incidence and risk factors of transition from Rp to a CTD were analysed by two independent reviewers. The main outcome was the rate of transition to a CTD; the secondary outcome was the evaluation of predictors. RESULTS Of 856 articles captured, 7 selected studies met the inclusion criteria. A total of 4051 patients with primary Rp (pRp) and 1220 transitions to overt CTDs were recorded. The mean incidence rate of transition from pRp to a CTD was 2.65/100 person-years (standard error [SE] 1.2, 95% confidence interval [CI] 0.44–5.73). A total of 657 patients with suspected secondary Rp (ssRp) had antinuclear antibodies (ANAs) and/or capillary abnormalities; 188 transitions to CTDs were recorded, the mean incidence rate of transition from ssRp to CTD was 11.01/100 person-years (SE 4.0, 95% CI 0.11–22.12), and 135 transitions to systemic sclerosis (SSc), giving a mean incidence rate of transition from ssRp to SSc of 5.7/100 person-years (SE 2.19, 95% CI 1.02–13.19). With respect to patients with pRp, having ANAs without capillary abnormalities was associated with a risk for developing a CTD (pooled relative risks [RR] 7.63, 95% CI 2.87–20.29), whereas capillary abnormalities without ANAs resulted in a weaker risk of CTD transition (RR 5.53, 95% CI 1.45–21.06). The coexistence of ANAs and abnormal capillaroscopy significantly increased the risk of transition to CTD (RR 16.96, 95% CI 6.61–43.55). CONCLUSIONS A low incidence rate of transition from pRp to overt CTD was found. In spite of a possible study selection bias, ssRp appears to have a strong risk of transition to a CTD when there is concomitant presence of ANAs and abnormal capillaroscopy.